Determinants of profitability in ACE market Bursa Malaysia: evidence from panel models - Ghasemi, Maziar; Ab Razak, Nazrul Hisyam (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examines factors affecting a firm’s profitability, such as liquidity, firm size, lagged profitability, growth, debt, and lagged debt, among firms listed in the ACE market of Bursa Malaysia. The sample in this study comprises 60 listed companies for the period 2009-2013. Two proxies for profitability, namely ROA and ROE, were examined using static and dynamic panel model estimators. The findings of the static panel models revealed that liquidity and size have positive significant effects on ROA, while the effects of growth and debt were negatively significant. Also, firm size and sales growth had significant effects on ROE. The findings obtained from the System Generalized Method of Moments system (GMM-SYS) indicated that sales growth and leverage had negative and significant effects on ROA and ROE, while firm size was significantly and positively related to profitability. The lagged leverage factor had an insignificant relationship with profitability. However, liquidity had a significant negative influence on ROA, but the effect of liquidity on ROE was insignificant. Finally, persistent profitability was observed over time for both proxies. The findings of this study provided consideration for the capital market investors to monitor the factors related to profitability in the firms listed on the ACE market.